Patient skin dose measurements using a cable free system MOSFETs based in fluoroscopically guided percutaneous vertebroplasty, percutaneous disc decompression, radiofrequency medial branch neurolysis, and endovascular critical limb ischemia. (8th January 2015) - Falco, Maria D.; Masala, Salvatore; Stefanini, Matteo; Fiori, Roberto; Gandini, Roberto; Bagalà, Paolo; Morosetti, Daniele; Calabria, Eros; Tonnetti, Alessia; Verona‐Rinati, Gianluca; Santoni, Riccardo; Simonetti, Giovanni
Abstract : The purpose of this work has been to dosimetrically investigate four fluoroscopically guided interventions: the percutaneous vertebroplasty (PVP), the percutaneous disc decompression (PDD), the radiofrequency medial branch neurolysis (RF) (hereafter named spine procedures), and the endovascular treatment for the critical limb ischemia (CLI). The X‐ray equipment used was a Philips Integris Allura Xper FD20 imaging system provided with a dose‐area product (DAP) meter. The parameters investigated were: maximum skin dose (MSD), air kerma (Ka, r), DAP, and fluoroscopy time (FT). In order to measure the maximum skin dose, we employed a system based on MOSFET detectors. Before using the system on patients, a calibration factor F c and correction factors for energy ( C kV ) and field size ( C FD ) dependence were determined. Ka, r, DAP, and FT were extrapolated from the X‐ray equipment. The analysis was carried out on 40 patients, 10 for each procedure. The average fluoroscopy time and DAP values were compared with the reference levels (RLs) proposed in literature. Finally, the correlations between MSD, FT, Ka, r, and DAP values, as well as between DAP and FT values, were studied in terms of Pearson's product‐moment coefficients for spine procedures only. An F c value of 0.20 and a very low dependence of C FD on field size were found. A third‐order polynomial function was chosen for C kV . The mean values of MSD ranged from 2.3 to 10.8 cGy for CLI and PVP, respectively. For these procedures, the DAP and FT values were within the proposed RL values. The statistical analysis showed little correlation between the investigated parameters. The interventional procedures investigated were found to be both safe with regard to deterministic effects and optimized for stochastic ones. In the spine procedures, the observed correlations indicated that the estimation of MSD from Ka, r or DAP was not accurate and a direct measure of MSD is therefore recommended. PACS number: 87